If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 4) + -5 = 2x + 13 Reorder the terms: 2(4 + x) + -5 = 2x + 13 (4 * 2 + x * 2) + -5 = 2x + 13 (8 + 2x) + -5 = 2x + 13 Reorder the terms: 8 + -5 + 2x = 2x + 13 Combine like terms: 8 + -5 = 3 3 + 2x = 2x + 13 Reorder the terms: 3 + 2x = 13 + 2x Add '-2x' to each side of the equation. 3 + 2x + -2x = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 0 = 13 + 2x + -2x 3 = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 3 = 13 + 0 3 = 13 Solving 3 = 13 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| n+5=9+2n-3-8 | | .5(4x-10)=52+3x | | 69=3v | | 3x-6+x+8=42 | | 5xy^2+3xy^2= | | -5w^2+23w-42=0 | | 11=4x-3y | | 0=-16t^2+50t+6 | | 5x-4=3x+2x+3-2+1 | | 72=5c+7c-2c | | n+5=-1-16 | | 2(-3a+5)=2y+3 | | 68=4v | | a(a^7+1)-7(a^7+1)=0 | | 4x-3=x-3+3x | | 3(4)-6+4+8=42 | | m+5=1 | | 12x-7=27x+3 | | -1x=13 | | 34a-4(5d+2)=36 | | 235=177-x | | -5n-15n=10 | | 6x-2=4x-(-2x+2) | | J=9(3.14)p | | 3x-3=2x-16 | | -5n-n=10 | | 3x-2=16-x^2 | | 185-u=252 | | 3x+5+6x=15 | | 14x+7-2=7 | | 11(y-2)=13(y+4) | | 3p^2+4p=8 |